MANAJEMEN PERENCANAAN KURIKULUM MERDEKA DI MTS AL AMIN: IMPLEMENTASI, TANTANGAN, DAN SOLUSI DALAM MENGINTEGRASIKAN NILAI KEISLAMAN: Manajemen Kurikulum; Kurikulum Merdeka; Pendidikan Islam; Profil Pelajar Pancasila - Lestari, Hana; Nufus, Hayatun; Rahmawati, Ima; Bahrun, Hasan (PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM, 2025)
This research aims to describe and analyze the management of Independent Curriculum planning at MTs Al Amin. In its implementation, curriculum planning is carried out through systematic stages that include needs analysis, preparation of learning programs, and curriculum development that integrates Islamic values and local character. The results of the study show that curriculum management at MTs Al Amin is carried out with a flexible and collaborative approach between the head of the madrasah and teachers. Despite the challenges related to the limitations of digital facilities, teachers in this madrasah have successfully implemented a curriculum with high adaptation to the principles of Freedom of Learning. The implementation of a project-based curriculum and strengthening the profile of Pancasila students are also reflected in the learning practices in this madrasah. The findings of this study provide an overview of how the planning management of the Independent Curriculum can be adapted and implemented effectively in the madrasah environment, taking into account internal and external factors that affect its success.